Perspectives of seed health in the genomic era - PRAKASH, H.S. (Indian Phytopathology, 2014)
Seed is a vital input in agriculture. The International seed trade has crossed 10,000 million USD in 2010 and the total estimated value of the domestic seed market among important countries is 44,925 million USD, India ranking 6th with a market of 2,000 million USD (International Seed Federation Seed Statistics, 2014). India is an important producer and exporter of seed. Many national and multi-national seed companies are operating in India. Hence it is important to meet the ational seed health quality standards to sustain the seed trade. Seeds are infected by fungi, bacteria, viruses and nematodes. The seed borne inoculum of pathogens may cause seed/seedling death resulting in poor plant stand, as well it may contribute to introduction and spread of disease. Thus seed health is of great concern to agrofood industry and regulatory authorities like quarantine and seed certification agencies. The seed industries are concerned with meeting the stringent International Phytosanitory regulations and to deliver sufficiently healthy seed to farmers and seed producers. It is difficult to control viral/bacterial diseases through prophylactic fungicide treatment. Hence preventive measures like avoidance of contaminated/infected planting material are preferred to manage the disease. In this background, testing of planting material for pathogen-free status gains significance.